Takhrij Hadits tentang Perempuan yang Salat di Masjid: Sebuah Wacana Hadits dalam Perspektif Gender - Ahmad Syukri (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2019)
This article tries to analyse a prophetic tradition concerning woman who perform their praying in the mosque. This study is done by implementing takhrij al hadits method. The result tenas to show that although women strongly suggested to pray at home, their praying in the mosque is quite acceptable.